Acupressure Application and Role of Nurse in Constipation Management - Mahinur Durmuş İskender; Nurcan Çalışkan (LookUs Bilisim A.S., 2020)
Constipation is an important symptom of functional disorders of the gastrointestinal system that affects individuals from all ages and causes a threat to health. The frequency of constipation increases with age and 40% of individuals who are 65 and older experience constipation. When the frequency of constipation in a hospital environment is examined, 71.7% of the cases are seen in surgery clinics, in 95% of patients with heart disease and in 100% of cancer patients. Non-pharmacological integrated methods have been widely used in health care in recent years. Acupressure, which is a treatment that is used to reduce the pain, to relax and relieve and reduce the symptoms by application of certain point pressures and scrubbing manipulations on the body's acupuncture meridians and meridians. Constipation is one of the areas of acupuncture which is frequently used in many different diseases and symptoms. Studies reported that the acupressure has positive effects on the constipation. Nurses should be knowledgeable about non-pharmacological methods in order to manage the problem of constipation which is among the common symptoms in the hospital. This article investigated the acupressure method known to be effective in preventing and eliminating constipation
Keywords: nursing; acupressure; R; Medicine; constipation; 3. Good health